Unveiling The Role of IT Capability in Human Resource Performance through Organizational Learning and Smart Working - Mar'atus Sholikah; Heru Sulistyo (Journal of Office Administration : Education and Practice, 2026)
This study aims to examine the strategic role of IT capability in improving human resource performance through organizational learning and smart working. In the context of digital transformation, organizations must not only adopt technology but also learn how to utilize information technology to support flexible and adaptive work patterns. This study investigates how IT capability functions as a strategic capability that promotes smart working and strengthens organizational learning to enhance performance. This quantitative approach research administered a survey to 139 employees of the Roudlotul Mubtadi’in Educational Foundation, which was implementing an electronic work system. The findings indicate that IT capability significantly influences human resource performance both directly and indirectly through smart working. The results confirm that smart working serves as an important operational mechanism that integrates technological capability with performance outcomes. Although organizational learning does not directly affect performance, it helps establish the foundation for flexible organizational capabilities, which in turn can enhance adaptability and responsiveness to changing market conditions. Overall, the findings suggest that IT capability functions as a strategic factor in enhancing human resource performance in the digital era, particularly when organizations combine it with smart working and organizational learning.